2014
DOI: 10.1002/wsb.429
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife management aims and ecological processes: A case study of kangaroos

Abstract: Wildlife management can be for conservation, sustainable utilization, and pest control. This study describes broad-scale patterns in the annual population growth rate (r) in 2 large mammals that are the focus of wildlife management, namely the western gray (Macropus fuliginosus) and the red kangaroo (M. rufus). The study also aims to determine the processes that generate the patterns, in particular weather and harvesting. The mean annual population growth rates were not different from zero (r $ 0) consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…Although SOI was commonly included in the best‐fitting models, its influence on population abundance was weak and variable, a result corroborated by other studies (e.g. Boyle & Hone 2014). Even though lagged rainfall was commonly included in the group of models with substantial support, its effect was only weakly positive on many kangaroo subpopulations.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although SOI was commonly included in the best‐fitting models, its influence on population abundance was weak and variable, a result corroborated by other studies (e.g. Boyle & Hone 2014). Even though lagged rainfall was commonly included in the group of models with substantial support, its effect was only weakly positive on many kangaroo subpopulations.…”
Section: Discussionsupporting
confidence: 79%
“…1984; Bayliss 1985; Jonzén et al . 2005; Boyle & Hone 2014). Accumulated monthly rainfall data were obtained from the SILO spatially interpolated daily rainfall datasets (gridded datasets) at a resolution of 0.05° latitude by 0.05° longitude (approximately 5 × 5 km) (Queensland Government 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a simplification of reality as studies have shown annual variation in reproductive output (Santos et al, 2006;Holland et al, 2009) and seasonality (Santos et al, 2006;Canu et al, 2015) due to resource availability. Resource-based changes in per-individual reproductive output would introduce additional variation in reproductive output across years, which would increase the uncertainty in our quantitative predictions (Boyle and Hone, 2014) but should not affect the relative effects of different treatments. Similarly, we did not account for potential effects of density-dependent reproduction, which could decrease our predicted rates of population decline (i.e., efficiency; Melero et al, 2015).…”
Section: When To Cullmentioning
confidence: 99%
“…In addition, despite considerable research effort devoted to understanding the ecology of kangaroos (e.g. Dawson 2012), and on-going monitoring of rangeland kangaroo populations (Industry and Development Assessment 2017; Natural Resources South Australia Arid Lands 2017; Office of Environment and Heritage 2017a; Department of Biodiversity, Conservation and Attractions 2019), there remain important sources of uncertainty surrounding the response of populations to management actions, for example the relative importance of compensatory versus additive mortality during phases of population increase and decrease (Boyle and Hone 2014), the impact of non-sex-biased culling on population viability (Shelly 1997) and the impacts of attempting to maintain populations above or below agreed thresholds (Chee and Wintle 2010).…”
Section: An Active Adaptive Management Framework For Kangaroosmentioning
confidence: 99%